Selecting Democracy Indicators for the modern University - Papanikolaou, Vaia; Yiannis Roussakis; Tzionas, Panagiotis (Academia, 2021)
The purpose of the proposed research is the application of suitable indicators, which measure the state of democracy, to the university field. Initially, an in-depth analysis of the features presented in six international organizations measuring democracy worldwide was performed. This revealed a sizeable set of significant and complementary indicators that constructed a conceptual framework for democratic institutions. Then, a model of the ‘democratic’ university was established with respect to its mission, operations and interactions, comprising a set of democratic characteristics. Interviews with academics from several European countries helped select those primary democracy indicators that can be best associated with the university characteristics. Interviews were analyzed using a Text Network Analysis algorithm, which represents texts as network graphs. Results show that monitoring these associations can reveal discrepancies and flaws that may degrade the university’s democratic operation and, also, helps to resolve conflicting demands when interacting with societal actors and the state. The size and variety of the examined datasets overcomes data bias, and the novelty of our approach lies in the fact that the graphical representations of the texts does not impose external semantic structures, thus avoiding subjectivity. This can have significant implications in assisting the complex policy formation processes within the university.
Keywords: Democratic indicators; Text Network analysis; university